Analisis Dampak Putusan Etik terhadap Keabsahan Putusan Lembaga Peradilan: Perbandingan Putusan Mahkamah Konstitusi dan Putusan Badan Peradilan dalam Lingkup Mahkamah Agung - Sidiq, Muhamad (Jurnal Konstitusi & Demokrasi, 2025)
Constitutionalism places the constitution as the supreme law that binds all state administrators, with the Constitutional Court (MK) as the guardian of the constitution through final and binding judicial review decisions. However, serious challenges have emerged regarding ethical violations by constitutional judges, such as in Decision No. 90/PUU-XXI/2023, which raises questions about the legitimacy and validity of the decision. This study employs a normative legal method with a doctrinal approach to analyze the applicability and impact of ethical rulings on MK decisions and compares them with ethical oversight and decision correction practices within the Supreme Court (MA). The findings indicate that ethical violations by MK judges only result in personal sanctions without invalidating the substance of the decision, while in the MA, although there is a mechanism for reviewing decisions related to ethical violations, its implementation is highly limited. This study recommends strengthening ethical oversight mechanisms that are more integrated with substantive review of decisions and developing an internal accountability system to maintain the integrity and legitimacy of the judicial institution without compromising legal certainty.